An analysis of environment stewardship projects implemented by the Catholic Church in Makindu sub-county, Makueni County, Kenya - Mbuthi, Peter Maithya; Kamwaria, Alex; Mbithi, Julius (Nairobi Journal of Humanities and Social Sciences, 2024)
The evidence of environmental degradation is all around us especially in the marginalized arid and semi-arid lands. There is a growing concern over environmental destruction due to human activities in the arid and semi-arid lands which has attracted a number of stakeholders and has specifically challenged the church to respond. The role of the church in environmental conservation is not yet much recognized in scholarship and secular agencies. A case study was conducted to investigate the role of the Catholic Church in environmental in Makindu sub-county. A qualitative design was used in the study using questionnaires, interviews, observations and secondary data as research instruments. To analyse the collected data phenomenological approach based on Edmund Hursels principles of analysis was employed. The study revealed that the catholic churches’ participation in environmental conservation is tremendous. The church is involved in environmental campaigns, environmental teachings, tree planting, at the pastoral level. This paper therefore has provided an insight into the critical role of the Catholic Church in playing in environmental conservation in Makindu sub-county.